2017
DOI: 10.3892/mmr.2017.6331
|View full text |Cite
|
Sign up to set email alerts
|

Matrine reduces the proliferation of A549 cells via the p53/p21/PCNA/eIF4E signaling pathway

Abstract: The aim of the present study was to investigate how matrine affects the proliferation of A549 human lung adenocarcinoma cells via the p53/p21/proliferating cell nuclear antigen (PCNA)/eukaryotic translation initiation factor 4E (eIF4E) signaling pathway. The effect of different concentrations of matrine on the proliferation of A549 cells was investigated using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The migration of A549 cells following exposure to varied concentrations of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 44 publications
(44 reference statements)
2
14
0
Order By: Relevance
“…Furthermore, matrine induced apoptosis and cell cycle arrest in TPC-1 cells. These results were consistent with those previously obtained in studies investigating other cancers ( 14 , 15 , 17 ,14).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, matrine induced apoptosis and cell cycle arrest in TPC-1 cells. These results were consistent with those previously obtained in studies investigating other cancers ( 14 , 15 , 17 ,14).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the PTEN/Akt signaling, miR-21 serves important roles in cancer growth, proliferation, migration and metastasis by targeting programmed cell death 4 and Sprouty RTK signaling antagonist 1, or by upregulating Bcl-2 indirectly ( 10 , 13 , 31 ). Overexpression of PTEN upregulates the p21/WAF1/CIP1 and p27/KIP1 pathways by dephosphorylating Akt to increase cell apoptosis and/or induce G1 phase arrest ( 17 , 23 ). These issues should be further investigated in thyroid cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of miRNA's KEGG pathway demonstrated that most of the target genes are enriched in Hippo signaling pathway and p53 signaling pathway, which are closely related to the proliferation and metastasis of cancer cells. Matrine plays an important role in regulating p53 signaling pathway to inhibit cell proliferation in liver cancer, lung cancer and esophageal cancer [80][81][82]. Besides, matrine can also promote colorectal cancer cell apoptosis via Hippo signaling pathway [83].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the anticancer activity of matrine. Lu et al had reported an induction of ~ 25% apoptosis in A549 after 48 h exposure to matrine [47], and Wang et el., have shown that long-term (48 h) exposure of matrine at high doses (2000 μg/ml) can induce moderate (15%) apoptosis in cisplatin-resistance A549 [48]. Other studies have shown that matrine at a dose of 100 μg/ml matrine for 48 h can diminish proliferation of cervical cancer cells by reducing the expression of matrix metalloproteinases through suppression of p38 signaling pathway [49].…”
Section: Discussionmentioning
confidence: 99%